Sosialisasi Peluang Usaha dan Strategi Pemasaran bagi Calon Wirausaha Muda dalam Meningkatkan Ketahana Ekonomi Rumah Tangga di Desa Mojowiryo Kecamatan Kemlagi Kabupaten Mojokerto - Sugeng Eko Yuli Waluyo; Ahfi Nova Ashriana; Elly Joenarni; Elok Cahyaning Pratiwi; Risa Amalia Muzrifah (Fakultas Teknik Universitas Cenderawasih, 2025)
This community service article is a qualitative research, containing efforts to enlighten through exploring business opportunities, fostering an entrepreneurial spirit for teenagers, especially administrators and members of the youth organization. This is done to help the government's program in reducing the impact of unemployment due to the many efficiencies carried out by companies that lay off their employees, eradicating poverty and strengthening food security. The method used is initial socialization about what entrepreneurship is, several new business opportunities that can be pursued as well as marketing strategies. In addition to socialization, there is also intensive mentoring and trying to provide examples of digital marketing. With this youth empowerment activity, it is hoped that it will open their insights and paradigms about the importance of rising from the slump due to unemployment, to becoming a successful entrepreneur in several varied business segments.